A new approach for constrained chaos synchronization with application to secure data communication - Hassan, Mohamed F.; Hammuda, Mohammad (Journal of the Franklin Institute, 2019)
In this paper, a new technique is introduced for chaos secure data communication. In this approach, in addition to the usually used techniques for data encryption, the concept of carrier encryption is introduced to increase the security level of the secure communication scheme. To fulfill this objective, at the transmitting end, two chaotic oscillators are coupled, and a set of inequality time dependent constraints with time dependent bounds is imposed on the generated chaotic signals. Moreover, to increase system complexity and its security level, the imposed set of constraints and their bounds are allowed to be changeable from one time period to another during the transmission process. As a result, the patterns of the generated chaotic signals are completely changed and the chaotic oscillator is completely encrypted. At the receiving end, the newly developed Constrained Smoothed Regularized Least Square (CSRLS) observer is used to synchronize the received constrained chaotic signals and hence retrieve the transmitted data. Using such an approach, the quality of the received information, measured by the Bit Error Rate (BER), is highly improved due to the superior performance of the developed CSRLS observer. The stability of the observer is analyzed, and simulation results are presented to show the efficiency and effectiveness of the proposed secure communication scheme.